Amyotrophic lateral sclerosis affects cortical and subcortical activity underlying motor inhibition and action monitoring. Issue 8 (24th April 2015) - Mohammadi, Bahram; Kollewe, Katja; Cole, David M.; Fellbrich, Anja; Heldmann, Marcus; Samii, Amir; Dengler, Reinhard; Petri, Susanne; Münte, Thomas F.; Krämer, Ulrike M.
Abstract Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by muscular atrophy, spasticity, and bulbar signs caused by loss of upper and lower motor neurons. Evidence suggests that ALS additionally affects other brain areas including premotor cortex and supplementary motor area. Here, we studied movement execution and inhibition in ALS patients using a stop‐signal paradigm and functional magnetic resonance imaging. Seventeen ALS patients and 17 age‐matched healthy controls performed a stop‐signal task that required responding with a button press to a right‐ or left‐pointing black arrow (go‐stimuli). In stop‐trials, a red arrow (stop‐stimulus) was presented shortly after the black arrow indicating to withhold the prepared movement. Patients had by trend higher reaction times in go‐trials but did not differ significantly in their inhibition performance. Patients showed stronger inhibition‐related activity in inferior, superior, and middle frontal gyri as well as in putamen and pallidum. Error‐related activity, conversely, was found to be stronger in healthy controls, particularly in the insula bilaterally. Patients also showed increased activity in the motor cortex during button presses. The results provide evidence for altered prefrontal and subcortical networks underlying motor execution, motor inhibition, and error monitoring in ALS. Hum Brain Mapp 36:2878–2889, 2015. © 2015 Wiley Periodicals, Inc.